Rewiring food systems to enhance human health and biosphere stewardship. (5th October 2017) - Gordon, Line J; Bignet, Victoria; Crona, Beatrice; Henriksson, Patrik J G; Van Holt, Tracy; Jonell, Malin; Lindahl, Therese; Troell, Max; Barthel, Stephan; Deutsch, Lisa; Folke, Carl; Haider, L Jamila; et al.
Abstract: Food lies at the heart of both health and sustainability challenges. We use a social-ecological framework to illustrate how major changes to the volume, nutrition and safety of food systems between 1961 and today impact health and sustainability. These changes have almost halved undernutrition while doubling the proportion who are overweight. They have also resulted in reduced resilience of the biosphere, pushing four out of six analysed planetary boundaries across the safe operating space of the biosphere. Our analysis further illustrates that consumers and producers have become more distant from one another, with substantial power consolidated within a small group of key actors. Solutions include a shift from a volume-focused production system to focus on quality, nutrition, resource use efficiency, and reduced antimicrobial use. To achieve this, we need to rewire food systems in ways that enhance transparency between producers and consumers, mobilize key actors to become biosphere stewards, and re-connect people to the biosphere.